Nasyiya1 , Renhart Jemi2*, Ahmad Mujaffar2 , Nuwa2 , Herianto2: UJI AKTIVITAS ANTI BAKTERI MINYAK ATSIRI DAN AMPAS DARI KULIT KAYU Cinnamomum sintoc Blume TERHADAP BAKTERI Staphylococcus aureus (Anti-Bacterial Activity Testing of Essential Oil and Drugs of Wood Skin From Cinnamomum sintoc Blume Against Bacteria of Staphylococcus aureus) - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2021)
This study aims to determine the antibacterial activity of essential oils and residue fromthe distillation of Sintok bark (C. sintoc Blume) against S. aureus bacteria. The researchwas carried out by distillation of sintok bark and macerating the dregs. Furthermore, theessential oil and extract the dregs were tested for antibacterial activity against S. aureus.Inhibition zone data were tabulated and analyzed by simple linear regression. The resultsshowed that the essential oil with the highest inhibition zone at a concentration of 20,000mg / L was 11.10 mm, As well as the inhibition zone dregs extract of 6.57 mm. Inconclusion, sintok wood essential oil is more active than its pulp against S. aureus. Inconclusion, sintuk wood essential oil is more active than the dregs extract against S.aureusKeywords : Antibacterial, essential oil, Cinnamomum sintoc, Staphyloccocus aureus